Analisis Tingkat Kelulusan Mahasiswa di Unisba dengan menggunakan Algoritma K-Means Clustering - Ayunia Khaerunnisa (Jurnal Riset Matematika, 2022)
Abstract. The graduation rate is very important to see academic success in the educational process at a university. In the academic environment at universities, especially in the mathematics study program at the Islamic University of Bandung, there are still problems regarding students who cannot complete their studies within the allotted time. The existence of these problems requires a method or technique that can classify students based on the SKS (Semester Credit Units) that have been taken and the IPK value so that the graduation time can be predicted. The technique used in this research is the clustering technique using the k-means algorithm which aims to find the graduation pattern of students who are still studying or have graduated on time according to the predetermined graduation year. Based on the policy of the mathematics study program the Islamic University of Bandung, each student has a minimum study load of 147 SKS that must be taken in 7 semesters or a maximum of 14 semesters and has a IPK minimum 2,00. The results of the study using data from active students in the 2015-2016 mathematics study program are known to be can grouped into three clusters including the first cluster is students who graduate early, the second cluster is students who graduate on time, and the third cluster is students who graduate more than four years. So the study program can find out which students are included in the three clusters and can be proposed to be used as input for decision makers. Abstrak. Tingkat kelulusan sangat penting untuk melihat keberhasilan akademik dalam proses pendidikan di suatu universitas. Dalam lingkungan akademik di perguruan tinggi, khususnya pada program studi matematika di Universitas Islam Bandung, masih terdapat permasalahan mengenai mahasiswa yang tidak dapat menyelesaikan studinya dalam waktu yang telah ditentukan. Adanya permasalahan tersebut maka membutuhkan suatu metode atau teknik yang dapat mengelompokkan mahasiswa berdasarkan SKS (Satuan Kredit Semester) yang telah ditempuh dan nilai IPK agar waktu kelulusan dapat diprediksi. Teknik yang digunakan dalam penelitian ini yaitu dengan teknik clustering dengan menggunakan algoritma k-means yang bertujuan untuk menemukan pola kelulusan mahasiswa yang masih menempuh pendidikan maupun sudah lulus tepat waktu sesuai tahun kelulusan yang sudah ditentukan. Berdasarkan kebijakan program studi matematika Universitas Islam Bandung, setiap mahasiswa memiliki beban studi minimal 147 SKS yang harus ditempuh dalam 7 semester atau maksimal 14 semester dan memiliki IPK minimal 2,00. Hasil penelitian dengan menggunakan data mahasiswa aktif pada program studi matematika 2015-2016 diketahui dapat dikelompokkan menjadi tiga cluster diantaranya cluster pertama adalah mahasiswa yang lulus lebih awal, cluster kedua adalah mahasiswa yang lulus tepat waktu, dan cluster ketiga adalah mahasiswa yang lulus lebih dari empat tahun. Sehingga prodi dapat mengetahui mahasiswa mana yang termasuk dalam ketiga cluster tersebut dan dapat diusulkan untuk dijadikan masukan bagi pengambil keputusan.